Optimization of Growth Media and Physical Condition in The Production of Sclerotium rolfsii Protein - Stefania - Nim: 10414027, Marchia
WHO predicted that meat consumption as protein source will increased until 2030. Although meat contains essential amino acids that are complete, the supply of meat requires quite a lot of time and resources. Consumption of meat also has a negative impact for human health as meat contain cholesterol (LDL). To resolve the issue, there has been research about alternative protein resources, in example, mycoprotein. As an alternative protein resource, mycoprotein has many advantages such as meat like textures, short production time, resource efficiency, low cholesterol content, and easily processed to be various types of food. This research focus on optimization of mycoprotein production from Sclerotium rolfsii. The anamorph of Athelia rolfsii is belong to Basidiomycota and chosen for its rapid growth in various types of nutritients. The optimization of growing media and physical factor such as agitation are done. As many as 243 types of media tested with 3 variations of complex carbon source (rice flour/B, tapioca flour/A, and corn starch/M; in 3 concentrations such as 5,10, and 15%), 3 variations of complex nitrogen source (egg/T, chicken broth/D, and fish broth/I; in 3 concentrations such as 2.5, 5, and 10%), and 3 types of sugar (glucose, sucrose, and dextrose in 2.5% concentration). Turns out that the radial growth and dry weight of Sclerotium rolfsii best on MIS 15:10 media. Next, the physical factor tested in 100,125, and 150 rpm, with observation in terms of protein content and dry weight for 9 days. Based on Bradford tests for protein content, optimum protein production occurs in 150 rpm after 6 days of incubation with total 27,53% (w/w) protein in fungal biomass.